Effects of the Self-Directed Individualized Education Program on Self-Determination and Transition of Adolescents With Disabilities. (December 2015) - Seong, Youjin; Wehmeyer, Michael L.; Palmer, Susan B.; Little, Todd D.
The 1990 Individuals with Disabilities Education Act (IDEA) reauthorization introduced transition mandates that included a "student involvement in transition planning" requirement, creating an emphasis on promoting such involvement so as to enhance the self-determination of students with disabilities and positive transition-related outcomes. This study used a randomized-trial control group design to study the impact of one widely used program to promote student involvement, the Self-Directed Individualized Education Program (IEP), on the self-determination and transition empowerment of youth with disabilities. A repeated-measures MANCOVA was conducted to determine the differences between an intervention group and the placebo-control group. Results showed that instruction using the Self-Directed IEP was significant on students' level of self-determination, and positive differences were found in transition knowledge when compared with a placebo-control group.